Membangun Generasi Digitalpreneur Melalui Pelatihan Keterampilan Digital Marketing bagi Badan Santunan Yatim, Margonda, Depok - Basudani, Wahid Akbar; Mulyadi, Harry; Simamora, Valentine Theresia; Purwanto , Obi Eko (Indonesian Journal of Society Engagement, 2024)
This Community Service activity aims to provide socialization and training for teenagers who are under the guidance of the Margonda Orphan Compensation Agency, Depok where children who take shelter in this institution need knowledge of digital skills in development efforts. The method used is by giving lectures or presenting material directly, consisting of an explanation of what digitalpreneur is to the use of e-commerce in building an online shop. By knowing the concept of digipreneur, teenagers can understand the potential of entrepreneurship which is supported by the ability to utilize technology.